Kualitas Pelayanan Program Samsat Setempoh Di Kantor UPT BAKUDA Wilayah Kabupaten Bangka - Sudarmawan; Putra, Raniasa; Mohamat, Joko (STISIPOL Pahlawan 12 Press, 2024)
This research aims to analyze and evaluate the service quality of the Samsat Setempoh Program implemented at the UPT BAKUDA Office in Bangka Regency. The Samsat Setempoh Program is a public service innovation that aims to facilitate the community in managing motor vehicle administration. The research uses a qualitative descriptive method by collecting data through observation, in-depth interviews, and documentation studies. The research sample consists of Samsat service officers and service users selected using purposive sampling technique. Service quality analysis was conducted using five SERVQUAL dimensions: tangible, reliability, responsiveness, assurance, and empathy. The results show that the implementation of the Samsat Setempoh Program at UPT BAKUDA Bangka Regency has been running quite effectively, however, there are still several aspects that need to be improved such as service speed, availability of supporting facilities, and integrated information systems. This research provides recommendations for program development to improve public service quality in the future